Forward-backward asymmetry in top quark-antiquark production - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Vertogradov, L. S.; et al. (Amer Physical Soc, 2011)
We present a measurement of forward-backward asymmetry in top quark-antiquark production in proton-antiproton collisions in the final state containing a lepton and at least four jets. Using a data set corresponding to an integrated luminosity of 5.4 fb(-1), collected by the D0 experiment at the Fermilab Tevatron Collider, we measure the t (t) over bar forward-backward asymmetry to be (9.2 +/- 3.7)% at the reconstruction level. When corrected for detector acceptance and resolution, the asymmetry is found to be (19.6 +/- 6.5)%. We also measure a corrected asymmetry based on the lepton from a top quark decay, found to be (15.2 +/- 4.0)%. The results are compared to predictions based on the next-to-leading-order QCD generator MC@NLO. The sensitivity of the measured and predicted asymmetries to the modeling of gluon radiation is discussed.